Analysis of microorganisms and drug-resistance mutations detected by probe-capture metagenomics among HIV-infected patients with pneumonia - Qianhui Chen; Qianhui Chen; Pingzheng Mo; Pingzheng Mo; Rongrong Yang; Rongrong Yang; Huan Xu; Huifang Liu; Zhongwei Zhang; Zhongwei Zhang; Qian Du; Qian Du; et al. (Frontiers in Microbiology)
BackgroundProbe-Capture Metagenomics is a newly developed method for detecting infectious pathogens. However, its application in HIV-infected patients with pulmonary infection remains limited. This study utilized Probe-Capture Metagenomics to analyze lung microbiomes and Drug Resistance Mutations of HIV and bacteria in people living with HIV (PLWH) with pneumonia.MethodsWe retrospectively investigated lung microorganisms in PLWH hospitalized at Zhongnan Hospital of Wuhan University. A combination of bronchoalveolar lavage fluid Probe-Capture Metagenomics and conventional microbiological tests were performed in all patients.ResultsA total of 91 patients were included in the study. Excluding the EB and Torque teno virus, at least two organisms were identified in 85 patients using Probe-Capture Metagenomics combined with conventional microbiological tests. The top six detected organisms were CMV, Pneumocystis jirovecii, Mycobacterium tuberculosis complex, HHV-7, Candida albicans and Aspergillus. For specific organisms, the detection rate of CMV and Candida albicans by Probe-Capture Metagenomics was significantly higher than that of conventional microbiological tests (p < 0.0001). Moreover, the detection rates of CMV (p = 0.0167) and Pneumocystis jirovecii (p = 0.04) in patients with CD4+T count ≥ 200 cells/μL were higher than that with CD4+T count < 200 cells/μL. Importantly, Probe-Capture Metagenomics can uncover potentially clinically relevant drug-resistance mutations linked to HIV and bacteria.ConclusionProbe-Capture Metagenomics provides a promising method of detecting suspected opportunistic infections in PLWH with pneumonia, especially for mixed infections and rare microorganisms. In addition, Probe-Capture Metagenomics was a potential valuable tool for genotyping resistance testing of HIV and bacteria.